A DESIGNER IN THE INTERSECTION OF ISLAMIC-OTTOMAN ARCHITECTURE: THE ARCHITECTURAL CONCEPT OF TURGUT CANSEVER (1920-2009) - Kolsal, Fatma; Üstün, Berna; Ulusoy, F.Özge Güven; Şensoy, Gamze (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
Architects in the history of architecture try to be understood by their ideas that their designs need to be present on earth. Turgut Cansever (1920-2009) is an important opponent architect who was prized by Aga Khan Awards for architecture three times in his professional life and established his architectural understanding of the architecture of Ottoman and Islamic culture. This study aims to describe the life and work of the architect and his opinion about Islamic-Ottoman Architecture. Setting his architectural conception on a broader belief, Cansever strengthens his apprehension of architecture with his practice and literature studies. This unique approach in his works is shaped by a point of view that criticizes modernity but aims to validate it by reinterpreting in line with Islamic architecture. The references in the background of the structures of Cansever is thought to be too complex to read at a time. The understanding of Cansever's original designer perspective will be possible through the discussion of his synthesis resulted from the thoughts of Islamic architecture, Ottoman Architecture and modern architecture, and their reflections on his structures.